2017
DOI: 10.21873/anticanres.11831
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Different Muscle-Relaxant Anesthetics on Growth, Migration and Invasion of Gastric Cancer Cells

Abstract: Our results are important in selecting the type and dose of anesthetic used for surgery of gastric cancer patients. An understanding of the effect of muscle-relaxant anesthetics and their impact on tumor metastasis is critical, since it provides insight into the appropriate anesthetic strategy that could improve long-term survival in some patients with gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…The wound was analyzed by Image J software (version 1.62; National Institute of Health, Bethesda, MD, USA). The invasion assay using transwell were performed as described previously (21).…”
Section: Methodsmentioning
confidence: 99%
“…The wound was analyzed by Image J software (version 1.62; National Institute of Health, Bethesda, MD, USA). The invasion assay using transwell were performed as described previously (21).…”
Section: Methodsmentioning
confidence: 99%
“… 32 Jiang et al pointed out that rocuronium promoted the growth, invasion and migration of gastric cancer cells SGC7901 and BGC823 in a dose-dependent fashion in an in-vitro model, while cisatracurium exerted no significant effect on gastric cancer cells at normal plasma concentrations, but enhanced the migration of SGC7901 and BGC823 cells in overdose. 14 The foregoing studies demonstrated that two different NMBAs worked differently on tumor cells: cisatracurium inhibited tumor cell growth and invasion, while rocuronium promoted proliferation and migration. In contrast, our study showed that the benzylisoquinoline had an unfavorable effect on the short-term outcomes of gastric cancer patients compared with the aminosteroid.…”
Section: Discussionmentioning
confidence: 97%
“…In order to satisfy the surgical requirements, we used a high NMBA dose of the benzylisoquinolines, which might lead to cancer cell migration and inflammatory changes, while the dose of aminosteroids used was low and did not reach the concentration that could effect changes in tumor cells. 14 On the other hand, we only included gastric cancer patients, and mainly targeted the effects of the agents on inflammation and immunity, and did not examine the changes at cellular and molecular levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was previously reported that propofol, which is one of the most common intravenous anesthetic agents used during cancer resection surgery, suppresses proliferation and invasion by downregulating ERK-vascular endothelial growth factor/matrix metallopeptidase-9 signaling in ECA-109 ESCC cells (21). Cis has been shown to inhibit the proliferation, invasion and migration of gastric cancer cells (22). In addition, emerging evidence indicates that Cis can suppress cancer cell proliferation, invasion and migration via upregulation of p53, and inhibits the aggressiveness of colorectal cancer (23).…”
Section: Introductionmentioning
confidence: 99%